MYKHAILO DRAHOMANOV’S ATTITUDE TO ÉMIGRÉ FORMS OF THE REVOLUTIONARY-LIBERATING ACT AT THE BEGINNING OF THE 1870S - Pikhmanets, R. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article deals with the peculiarities of Mykhailo Drahomanov’s social-political tactics at the beginning of the 1870s, in particular his attitude to the émigré way of a revolutionary struggle. Then Drahomanov in his words denied appropriate forms, means and methods determinedly and peremptorily, though secretly he had already begun to think over the plan of a publishing center abroad. Such an ambiguous behavioral matrix was defined by the vision of perspectives of a national-liberating movement and by his “double” position in Ukrainophilia: the leader of its “left” wing, who above all placed the rescue of the Russian Empire via its reformation.